CRASHWORTHINESS AND LIGHT WEIGHT DESIGN OF BODY IN WHITE BASED ON HIGH STRENGTH STEEL AND FILLING MATERIALS - 姚宙; 郝玉敏; 李亦文; 李红建 (Jixie qiangdu)
Structure of vehicle body is designed to absorb kinetic energy,transform impact force and keep survival space during crash. Light weight design of BIWcan realize better power performance and fuel economy,decrease exhaust emission. In this paper,collision of vehicle body structure is decomposed into axial crushing and transverse bending. Thin walled structure’s ability inenergy absorption and bending resistanceis researched,which is based on high strength steel and different filling materials. After applied the research conclusion in a SUV’s body optimization,the crash simulation result shows that it improved passive safety and reduced body weight effectively.